Analisis Kinerja Program Keluarga Harapan (PKH) Menurut Ekonomi Islam - Y, Yuslimah; Z, Zuwardi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The safety of citizens is the dream of every nation. At the global level, Indonesia is at a much lower level than neighboring countries. In the global earth condition, Indonesia cannot be said to be a failed state, nor a country that is burdened with debt that is extinguished, but it must be recognized and watched out for that Indonesia is actually close to that situation. The PKH program has been around since 2007 in Indonesia, this assistance is a conditional assistance program. What is interwoven in the community is a lack of mastery of the purpose of the PKH assistance, caused by little insight and lack of socialization from the PKH assistance caregivers to the community. The PKH program in Jorong VII Polongan 2 Nagari Atasng Mantinggi Utara, Rao District, Pasaman Regency has been running since 2015. Due to the large number of poor people and low levels of education. with the existence of the Dream Family Program (PKH) it is hoped that it can help poor families in Jorong VII Polongan 2 Nagari Atasng Mantinggi Utara, Rao District, Pasaman Regency and children can study with free education and health assistance or at least reduce school fees, and for pregnant women or those with babies and the elderly can get good facilities and services in the health sector. In this case, the research informants are the community who welcomed the PKH encouragement and PKH Adjutants in Jorong VII Polongan 2. The Information Collection Method used by researchers to accumulate information is the following are some of the information collection methods that researchers use in conducting this research, namely, Monitoring is an observation that is carried out directly in the square. And directly observing some of the initial methods of implementing PKH in Nagari Atasng Mantinngi. Questions and answers Questions and answers are conversations with special meanings.